Incidence of Post-extubation Stridor in Infants With Cuffed vs. Uncuffed Endotracheal Tube: A Retrospective Cohort Analysis - Bibl, Katharina; Pracher, Lena; Küng, Erik; Wagner, Michael; Roesner, Imme; Berger, Angelika; Hermon, Michael; Werther, Tobias (Frontiers in Pediatrics, 2022)
Background: Endotracheal intubation is a common procedure in Neonatal Intensive Care. While cuffed endotracheal tubes (ETT) are the standard of care in adults and children, their use in infants is controversial. The aim of this study was to compare the incidence of post-extubation stridor between uncuffed and cuffed ETTs in infants. We further evaluated the safety of cuffed ETTs in infants with a bodyweight between 2-3kg and performed baseline analysis on development of subglottic stenosis. Methods: In this retrospective study, we screened all infants admitted to two NICUs of the Medical University of Vienna between 2012 and 2019.The study cohort was screened twice: In the first screening we selected all infants who underwent the first intubation when attaining a bodyweight > 2 kg (but <6 kg) to analyze the incidence of post-extubation stridor and only considered the first intubation of each included infant. Post-extubation stridor was defined as the administration of either epinephrine aerosol or any corticosteroid within six hours post-extubation. In the second screening we searched for all infants diagnosed with acquired severe subglottic stenosis during the study period regardless their bodyweight and numbers of intubations. Results: A total of 389 infants received at least one intubation during the study period. After excluding infants who underwent the first intubation below a bodyweight of 2kg, 271 infants remained for final analysis with an average gestational age of 38.7 weeks at the time of intubation. Among those, 92 (33.9%) were intubated with a cuffed and 179 (66.1%) with an uncuffed ETT. Seven infants (2.6%) developed a clinically significant stridor: five of those were intubated with a cuffed and two with an uncuffed ETT (71.4% versus 28.6%, p=0.053). All of them had a bodyweight > 3 kg at the time of intubation. Infants who developed subglottic stenosis were more often intubated with an uncuffed ETT. Conclusion: In this study, no difference in the incidence of post-extubation stridor between cuffed and uncuffed ETTs in infants with a bodyweight from 2 to 6kg could be found. The use of cuffed ETTs does not exhibit higher risk for the acquired subglottic stenosis in this cohort.